Examining the exercise dose-response using cardiac autonomic activity in female university ice hockey players - Peterson, M. L.; Monforton, P. E.; Bain, A. R.; Milne, K. J.; Perrotta, A. S. (Sports, 2025)
Female university ice hockey players experience elevated and sustained cardiovascular stress during training and competition. There remains limited research on the "exercise dose-response" in female ice hockey players. The purpose of this study was to examine daily and weekly changes in cardiac autonomic activity across a competitive season, and to examine its association with accumulated exercise stress. Twenty-one female ice hockey players wore chest strap heart rate monitors to quantify exercise heart rate dynamics into a training load (TL) metric and time (min) performing high-intensity activity (HIA) during training and competition. Cardiac autonomic activity was expressed as both resting heart rate (RHR) and the root mean squared of successive R-R intervals (rMSSD) and was recorded immediately upon awakening each morning. The association between HRV and both TL (r = -0.420, p = 0.058) and HIA (r = -0.420, p = 0.058) was observed. The association between RHR and both TL (r = 0.109, p = 0.638) and HIA (r = 0.150, p = 0.516) was observed. rMSSD fell below the typical error for ~50% of games. In conclusion, HRV demonstrated greater sensitivity to exercise stress than RHR for quantifying the dose-response to on-ice exercise stress.